Follistatin Attenuates Myocardial Fibrosis in Diabetic Cardiomyopathy via the TGF-β–Smad3 Pathway - Wang, Yinhui; Yu, Kun; Zhao, Chengcheng; Zhou, Ling; Cheng, Jia; Wang, Dao Wen; Zhao, Chunxia (Frontiers in Pharmacology, 2021)
Follistatin (FST) is an endogenous protein that inhibits the TGFβ superfamily irreversibly and plays an anti-fibrosis role in other diseases. However, the role of follistatin in diabetic cardiomyopathy remains unclear. In this study, we investigated the effects of follistatin on diabetic cardiomyopathy. Expression of follistatin was down-regulated in in the heart of db/db mice. Remarkably, overexpressing follistatin efficiently protected against cardiac dysfunction、In addition, overexpression of follistatin promoted cardiac hypertrophy with unchanged expression of ANP、BNP. Furthermore, follistatin reduces cardiac fibrosis as well as the production of reactive oxygen species (ROS) and enhanced MMP9 activity in db/db mice heart. We also observed that overexpressing follistatin decreased the level of TGFβ superfamily and the phosphorylation of Smad3, consistently, experiments in vitro also verify above results. Our findings revealed a cardioprotective role of follistatin in attenuating diabetic cardiomyopathy by its anti-fibrosis effects through TGFβ-Smad3 pathway and provided a promising therapeutic strategy for diabetic cardiomyopathy.